Validity Of Urine Dipstick Parameters In Identifying Urinary Tract Infections - Abbas, Muhammad Bilawal; Jalil, Aneza; Shafi, Fiza; Sufyan, Ali; Talpur, Hameer; Jamal, Ali Murad (Journal of Rawalpindi Medical College, 2025)
Objectives: To evaluate the diagnostic accuracy of urine dipstick parameters using semi-quantitative urine culture as the reference standard in the assessment of UTI. Methods: A cross-sectional validation study was conducted over 12 months in the Department of General Medicine in a public sector tertiary care hospital in Islamabad. A total of 303 cases suspected of having UTI were included. Combur10 Roche dipstick was used as a diagnostic test dipstick for the detection of urine leucocyte esterase and Urine nitrite. Cystine-lactose electrolyte deficient agar (CLED) media was used for quantitative culture of urinary microorganisms, the results of which were considered the gold standard. Results: 149 were females with a mean age of 50±20 years, while 154 participants were males with a mean age of 49±24 years. 42.6% (N=129) of the population studied had a positive result for urine culture with the most commonly isolated organism being klebsiella species (8.3%). The most specific parameter was the combination of nitrite positive and leucocyte esterase positive with a specificity of 98.9% (95% CI= 96.5-99.8%). The least specific results were those that were either nitrite positive or leucocyte esterase positive, with a specificity of 75.9% (95% CI= 69.2-81.8). Overall sensitivity of dipstick analysis was relatively poor. Conclusion: The combination of both the dipstick parameters, nitrite and leucocyte esterase showed better accuracy in terms of specificity and therefore ruling in the presence of UTI. The sensitivity, however, was generally poor, and it can be inferred that the dipstick is not a useful investigation in successfully ruling out the presence of UTI, urine culture must therefore be performed in highly suspicious cases. Keywords: Klebsiella, Pseudomonas, Urinary Tract Infections, bacteriuria, Escherichia coli